A review on non-metal and metal doped ZnO: Fundamental properties and applications - Patil Preeti M.; Sannakki Basavaraja; Mathad Shridhar N.; Veena E.; Gandad Sheela (Acta Periodica Technologica, 2023)
Several non-metal and metal doped ZnO nanoparticles were produced by a variety of routes, including Sol-gel, hydrothermal, and combustion methods. The methods of synthesis, characterization, and applications of these nanoparticles were surveyed and summarised in this review. This study will improve our understanding of developments in doped ZnO and assist in the creation of new ZnO-based materials with improved structural, photocatalytic, and antimicrobial properties.